2020
DOI: 10.1111/pce.13964
|View full text |Cite
|
Sign up to set email alerts
|

Acclimatisation of guard cell metabolism to long‐term salinity

Abstract: Stomatal movements are enabled by changes in guard cell turgor facilitated via transient accumulation of inorganic and organic ions imported from the apoplast or biosynthesized within guard cells. Under salinity, excess salt ions accumulate within plant tissues resulting in osmotic and ionic stress. To elucidate whether (a) Na+ and Cl− concentrations increase in guard cells in response to long‐term NaCl exposure and how (b) guard cell metabolism acclimates to the anticipated stress, we profiled the ions and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 87 publications
1
8
0
Order By: Relevance
“…Guard cells of the saltsensitive Arabidopsis cv Col-0 we investigated did not make use of this salt tolerance mechanism but increased expression of the K + release channel GORK. This finding is supported by a study on guard cells of the glycophyte Vicea faba which also cannot maintain a high K + : Na + ratio under salt stress (Franzisky et al, 2020). Patch-clamp studies on guard cells of the halophyte A. tripolium and the nonhalophyte A. amellus species have shown that both guard cell types are equipped with a similar array of cation channels, but their activities are differentially regulated by Na + in the two species, ultimately leading to a differential stomatal response (V ery et al, 1998).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Guard cells of the saltsensitive Arabidopsis cv Col-0 we investigated did not make use of this salt tolerance mechanism but increased expression of the K + release channel GORK. This finding is supported by a study on guard cells of the glycophyte Vicea faba which also cannot maintain a high K + : Na + ratio under salt stress (Franzisky et al, 2020). Patch-clamp studies on guard cells of the halophyte A. tripolium and the nonhalophyte A. amellus species have shown that both guard cell types are equipped with a similar array of cation channels, but their activities are differentially regulated by Na + in the two species, ultimately leading to a differential stomatal response (V ery et al, 1998).…”
Section: Discussionmentioning
confidence: 65%
“…Guard cells of the salt‐sensitive Arabidopsis cv Col‐0 we investigated did not make use of this salt tolerance mechanism but increased expression of the K + release channel GORK. This finding is supported by a study on guard cells of the glycophyte Vicea faba which also cannot maintain a high K + : Na + ratio under salt stress (Franzisky et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sour passion fruit leaf gas exchange was negatively affected by exposure to salt stress. This result is a consequence of the effects of salt accumulation in the soil, which reduces osmotic potential and limits the absorption of water by the plant, leading to stomatal closure (Figure 4A) and reduced transpiration (Figure 4B) (FRANZISKY et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In C4 plants, phosphoenolpyruvate carboxylase (PEPCase) is more sensitive to salt than Rubisco (Chiconato et al 2021). The partial or complete closure of stomata also aggravates the effects of salinity stress that limits CO2 availability (Franzisky et al 2021). The storage of carbohydrates is also hampered by salt stress as evident from the microscopic observations in Ulva prolifera.…”
Section: Characteristics Underlying Sensitivity Of Photosynthesis To ...mentioning
confidence: 99%